The Utilization of Edamame (Glycine max (L.) Merr) And Red Bean (Phaseolus vulgaris) As A Functional Beverage - Melanie Cornelia; Soraya Triesly Lessy (Chemistry Education Program, the University of Mataram, 2018)
Indonesia had the big potency to produce red beans and edamame beans, but its utilization regarding functional food was not optimal. This research was intended for development combining red and edamame beans to become a new functional beverage product. The ratio of edamame milk to red bean milk (100:0, 75:25, and 50:50) and cooking temperature 90 oC has been selected based on SNI soymilk. During storage, a phase separation happened. Consequently, stabilizer should be added to improve its stability. Three types of stabilizers were used,CMC 0.1 %, 0.2%, and 0.3 %, xanthan gum (XG), and guar gum (GG) 0.025 %, 0.05 %, and 0.1 %, respectively. The best formulation was milk ratio 75:25 with 90 oC and addition of XG 0.05 %. The dietary fiber analysis for milk formulation was 4.46 % therefore it was categorized as a functional beverage.